Examining Menstrual Tracking to Inform the Design of Personal Informatics Tools - Epstein, Daniel A; Lee, Nicole B; Kang, Jennifer H; Agapie, Elena; Schroeder, Jessica; Pina, Laura R; Fogarty, James; Kientz, Julie A; Munson, Sean A (Proceedings of the SIGCHI conference on human factors in computing systems. CHI Conference, 2017)
We consider why and how women track their menstrual cycles, examining their experiences to uncover design opportunities and extend the field's understanding of personal informatics tools. To understand menstrual cycle tracking practices, we collected and analyzed data from three sources: 2,000 reviews of popular menstrual tracking apps, a survey of 687 people, and follow-up interviews with 12 survey respondents. We find that women track their menstrual cycle for varied reasons that include remembering and predicting their period as well as informing conversations with healthcare providers. Participants described six methods of tracking their menstrual cycles, including use of technology, awareness of their premenstrual physiological states, and simply remembering. Although women find apps and calendars helpful, these methods are ineffective when predictions of future menstrual cycles are inaccurate. Designs can create feelings of exclusion for gender and sexual minorities. Existing apps also generally fail to consider life stages that women experience, including young adulthood, pregnancy, and menopause. Our findings encourage expanding the field's conceptions of personal informatics.